PENGARUH KEPEMIMPINAN, DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA KANTOR PDAM DI KABUPATEN SITUBONDO - Laia, Stiven Mawati; Soeliha, Siti; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
PDAM Tirta Baluran Situbondo is one of the efforts to provide access to clean water for Situbondo residents. The purpose of this research is to analyze and test the influence of leadership, work discipline and organizational culture on job satisfaction with work motivation as an intervening variable at the PDAM office in Situbondo Regency. The population in this study was PDAM Tirta Baluran Situbondo. Data analysis and hypothesis testing in this research used the Partial Least Squares Structural Equation Model (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that leadership has a negative but not significant effect on work motivation, work discipline has a significantly positive effect on work motivation, organizational culture has a significantly positive effect on work motivation, leadership has a negative but not significant effect on job satisfaction. , Work discipline has a significant negative effect on job satisfaction, Organizational culture has a significant positive effect on job satisfaction, Work motivation has a significant positive effect on job satisfaction, Leadership has a negative but not significant effect on job satisfaction through work motivation, Work discipline has a positive but not significant effect on satisfaction. work through work motivation, organizational culture has a significant positive effect on job satisfaction through work motivation.